A Simple Sonication Assisted Solvent Blending Route for Fabrication of Exfoliated Polystyrene (PS)/Clay Nanocomposites: Role of Various Clay Modifiers. (2018) - Pugazhenthi, G.; Suresh, Kelothu; Vinoth Kumar, R.; Kumar, Manish; Rajkumar Surin, Ritu
Abstract: This work attempts to study the properties of polystyrene (PS) nanocomposites prepared with 3 wt.% nanoclay containing four different organomodifiers such as (25-30 wt.% trimethyl stearly ammonium (Clay 1), 25-30 wt.% octadecylamine (Clay 2), 25-30 wt% methyl dihydroxyethyl hydrogenated tallow ammonium (Clay 3) and 35-45 wt.% dimethyl dialkyl (C14-C18) amine (Clay 4). Various PS nanocomposites were synthesized by ultrasonication assisted solvent-based mixing technique using xylene as solvent. Structural, thermal and rheological properties of PS nanocomposites were analyzed by XRD, TEM, FTIR, TGA and rotational rheometer. TEM images affirmed the formation of partially exfoliated structure of PS nanocomposites with these clays. All the PS/organoclay nanocomposites are thermally more stable than that of pristine PS. When 15% weight loss is taken as a reference point, the degradation temperature of PS nanocomposites prepared with clay 1 is about 18.1 °C higher than that of pristine PS. The thermal degradation kinetics of different nanocomposites is also determined. It is observed that the rheological moduli and complex viscosity of PS/organoclay nanocomposites are more than that of pristine PS in the frequency sweep at a fixed temperature of 190 °C.